The pathogenesis and therapeutic implications of metabolic reprogramming in renal cell carcinoma - Yifan Zhang; Shengli Zhang; Hongbin Sun; Luwei Xu (Cell Death Discovery)
Abstract Renal cell carcinoma (RCC), a therapeutically recalcitrant genitourinary malignancy, exemplifies the profound interplay between oncogenic signaling and metabolic adaptation. Emerging evidence positions metabolic reprogramming as a central axis of RCC pathogenesis, characterized by dynamic shifts in nutrient utilization that transcend canonical Warburg physiology to encompass lipid anabolism, glutamine auxotrophy, and microenvironment-driven metabolic plasticity. This orchestrated rewiring of cellular energetics sustains tumor proliferation under hypoxia while fostering immunosuppression through metabolite-mediated T cell exhaustion and myeloid-derived suppressor cell activation. Crucially, RCC exhibits metabolic heterogeneity across histological subtypes and intratumoral regions—a feature increasingly recognized as a determinant of therapeutic resistance. Our review systematically deciphers the molecular architecture of RCC metabolism, elucidating how VHL/HIF axis mutations, mTOR pathway dysregulation, and epigenetic modifiers converge to reshape glucose flux, lipid droplet biogenesis, and amino acid catabolism. We present novel insights into spatial metabolic zonation within RCC tumors, where pseudohypoxic niches engage in lactate shuttling and cholesterol efflux to adjacent vasculature, creating pro-angiogenic and immunosuppressive microdomains. Therapeutically, we evaluate first-in-class inhibitors targeting rate-limiting enzymes in de novo lipogenesis and glutamine metabolism, while proposing biomarker-driven strategies to overcome compensatory pathway activation. We highlight the synergy between glutaminase inhibitors and PD-1 blockade in reinvigorating CD8+ T cell function, and the role of lipid-loaded cancer-associated fibroblasts in shielding tumors from ferroptosis. Finally, we outline a translational roadmap integrating multi-omics profiling, functional metabolomics, and spatial biology to match metabolic vulnerabilities with precision therapies.